Investigation of magnesium nitrate hexahydrate based phase change materials containing nanoparticles for thermal energy storage. (21st August 2019) - Wang, Hui; Guo, Lijiang; Liu, Kaiqi; Song, Zichen; Wu, Liu; Fang, Minghao; Li, Jianqiang
Abstract: The magnesium nitrate hexahydrate (MNH) based composite phase change materials (PCMs) have been prepared by adding carboxyl methyl cellulose (CMC) as thickening agent. Different mass fractions of nanoparticles (nanosilver, nanocopper and graphene) have been added independently to enhance the thermal conductivities. The viscosities have been measured for the pure MNH and MNH/CMC composites at liquid state. The thermal conductivities of the solid phase pure MNH, MNH/CMC and MNH/CMC/Nanoparticle composites also have been measured by Hotdisk Thermal Constant Analyzer. It is found that the addition of CMC has little effect on the thermal conductivity of the solid state MNH based composite PCMs, while decreases the thermal conductivity of the liquid PCM. The addition of nanoparticles enhanced the thermal conductivity of the MNH based PCM composites dramatically. Among the prepared PCM composites, the addition of 1.5 wt% graphene, namely MNH/CMC/1.5 wt% graphene, shows the optimal characteristic that the thermal conductivity is improved to 0.807 W · m −1 · K −1 from 0.338 W · m −1 · K −1, and the supercooling degree is also decreased to 2.73 °C from 23.12 °C which shows the graphene nanoparticles can also act as a nucleating agent, compared with the pure MNH. Meanwhile, for the optimal composite PCM, the density is increased with the increase of pressure on the constant temperature and the thermal conductivity is increased with the increase of density. After 50 thermal cycles, the phase change enthalpy of MNH/CMC/1.5 wt% graphene composite is only decreased by 4.0%, much lower than the decreased value 16.8% of pure MNH. The results above conformed that the MNH/CMC/Graphene composite is promising to be used for building heating.